Q: -x2 plus 6x plus 16

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

16 + 6x - x2 = 16 + 8x - 2x - x2 = 8*(2 + x) - x*(2 + x) = (8 - x)*(2 + x)

x2 - 6x - 16 = (x - 8)(x + 2)

x2 + 6x = x*(x + 6)

x2 + 6x = 7 ⇒ x2 + 6x + 9 = 7 + 9 ⇒ (x + 3)2 = 16 ⇒ x + 3 = ±4 ⇒ x = -7 or 1

x3 + x2 - 6x + 4 = (x - 1)(x2 + 2x - 4)

Related questions

x2 + 6x = 16=> x2 + 6x - 16 = 0=> x2 + 8x -2x - 16 = 0=> (x+8)(x-2) = 0=> x = -8 or x = 2So, the solutions of the quadratic equation x2 + 6x = 16 are -8 and 2.

16 + 6x - x2 = 16 + 8x - 2x - x2 = 8*(2 + x) - x*(2 + x) = (8 - x)*(2 + x)

x2 - 6x - 16 = (x - 8)(x + 2)

-((x + 2)(x - 8))

x2 + 6x = x*(x + 6)

x2 + 6x = 7 ⇒ x2 + 6x + 9 = 7 + 9 ⇒ (x + 3)2 = 16 ⇒ x + 3 = ±4 ⇒ x = -7 or 1

x2 + 6x + 8 = (x + 4)(x + 2)

x3 + x2 - 6x + 4 = (x - 1)(x2 + 2x - 4)

x2 + 6x + 9 = 81 x2 + 6x = 72 x2 + 6x - 72 = 0 (x+12)(x-6) = 0 x= -12, 6 (two solutions)

x2 + 6x + 5 can be factored into (x+1) (x+5)

x2 - 6x = 16 ∴ x2 - 6x + 9 = 25 ∴ (x - 3)2 = 25 ∴ x - 3 = 25 ∴ x = 28

324